2016
DOI: 10.1016/j.dib.2016.10.025
|View full text |Cite
|
Sign up to set email alerts
|

Data on spermatogenesis in rat males gestationally exposed to bisphenol A and high fat diets

Abstract: This data article contains supporting information regarding the research article entitled “High butter-fat diet and bisphenol A additively impair male rat spermatogenesis” (P. Tarapore, M. Hennessy, D. Song, J. Ying, B. Ouyang, V. Govindarajah, et al.,) [1]. Sprague–Dawley females were fed AIN, high fat butter, 17α-ethinyl estradiol, or high fat butter plus four bisphenol A doses (2500 µg/kg bw-d, 250 µg/kg bw-d, 25 µg/kg bw-d, and 2.5 µg/kg bw-d) before and during pregnancy. All diets were switched to AIN aft… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
3
1

Relationship

2
2

Authors

Journals

citations
Cited by 4 publications
(8 citation statements)
references
References 3 publications
0
7
1
Order By: Relevance
“…There is very little information on the food/diet fed to these rodents. It has been shown that the fatty acid content of diets could be an important source of experimental variation impacting spermatogenesis [ 23 , 131 , 132 , 133 , 134 , 135 , 136 , 137 , 138 ].…”
Section: Studies Linking Environmentally Relevant Exposure To Malementioning
confidence: 99%
See 1 more Smart Citation
“…There is very little information on the food/diet fed to these rodents. It has been shown that the fatty acid content of diets could be an important source of experimental variation impacting spermatogenesis [ 23 , 131 , 132 , 133 , 134 , 135 , 136 , 137 , 138 ].…”
Section: Studies Linking Environmentally Relevant Exposure To Malementioning
confidence: 99%
“…Any changes in the hormone levels or receptor expression could result in impaired spermatogenesis. In male pups gestationally exposed to Bisphenol A, our laboratory experiments have shown loss of estrogen receptor beta protein in round spermatids and increased aromatase expression on the acrosomes of the developing spermatids [ 131 , 132 ]. A more thorough investigation of the expression of nuclear receptors estrogen receptor beta, AR, and aromatase in the PFOS/PFOA-exposed dividing, differentiating, and maturing germ cells, as well as Leydig and Sertoli cells within the seminiferous tubule, is thus lacking.…”
Section: Mechanism Of Action Of Pfos and Pfoamentioning
confidence: 99%
“…The animal usage and care protocols were approved by the Institutional Animal Care and Use Committee at the University of Cincinnati and were in compliance with NIH guidelines. As outlined in our previous publication [ 15 , 26 ], female Sprague-Dawley (SD) rat dams were housed under BPA-free conditions [ 15 , 33 ], and randomly placed into groups according to the in utero diet exposure for male offspring: (1) the American Institute of Nutrition (AIN) group was exposed to a modified open standard diet (product #D04042310 AIN 93G (Research Diets, Inc., New Brunswick, NJ, USA), 10 kcal% butterfat) certified to contain no phytoestrogens; (2) the BPA group was exposed to the test compound BPA at 25 µg/kg body weight per day (kg bw-d), which was directly incorporated into the unsupplemented (AIN) pellet diet; (3) the HFB group was exposed to 39 kcal% butterfat, which was directly incorporated into the unsupplemented (AIN) pellet diet; and (4) the HFB + BPA group was exposed to 25 µg/kg bw-d BPA and 39 kcal% butterfat. BPA-free conditions imply special cages and water sources/bottles that are certified BPA-free, and a separate room with filters for this study.…”
Section: Methodsmentioning
confidence: 99%
“…Pregnancy is a window for susceptibility to environmental toxicants, and exposure to BPA during pregnancy has been linked to adverse outcomes at birth and later in life [ 15 , 25 , 26 , 27 , 28 , 29 , 30 , 31 , 32 ]. In particular, we found that embryonic exposure to BPA (and HFB) influences spermatogenesis in the exposed F1-generation offspring as they become middle aged [ 15 , 33 ], and also under conditions that mimic aging, such as exposure to testosterone plus estradiol-17β (T + E2).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation